2020
DOI: 10.1371/journal.pone.0232189
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the epithelial barrier and immune signatures in the pathogenesis of equine insect bite hypersensitivity

Abstract: Insect bite hypersensitivity (IBH) is a Th-2, IgE-mediated dermatitis of horses caused by bites of insects of the genus Culicoides that has common features with human atopic dermatitis. Together with Th-2 cells, the epithelial barrier plays an important role in development of type I hypersensitivities. In order to elucidate the role of the epithelial barrier and of the skin immune response in IBH we studied the transcriptome of lesional whole skin of IBH-horses (IBH-LE; n = 9) in comparison to non-lesional ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 57 publications
1
26
0
1
Order By: Relevance
“…23 This finding has been confirmed in a transcriptome study, where IL-13 as well as its receptor transcripts IL13RA1 and IL13RA2 (Figure 1) were upregulated in CH lesional skin compared to skin from healthy controls. 17 This is in line with recent studies in humans, where IL-13 has been suggested to be the key Th2 cytokine driving inflammation in the periphery, while IL-4 has a more central effect. 24 IL-13 is thought to play a major role in the inflammatory reaction underlying human atopic dermatitis (AD), where IL-13 is overexpressed locally and has a significant impact on the recruitment of inflammatory cells, contributing to alterations of the skin microbiome and to a decrease in the epidermal barrier function.…”
Section: T Lymphocytessupporting
confidence: 89%
See 2 more Smart Citations
“…23 This finding has been confirmed in a transcriptome study, where IL-13 as well as its receptor transcripts IL13RA1 and IL13RA2 (Figure 1) were upregulated in CH lesional skin compared to skin from healthy controls. 17 This is in line with recent studies in humans, where IL-13 has been suggested to be the key Th2 cytokine driving inflammation in the periphery, while IL-4 has a more central effect. 24 IL-13 is thought to play a major role in the inflammatory reaction underlying human atopic dermatitis (AD), where IL-13 is overexpressed locally and has a significant impact on the recruitment of inflammatory cells, contributing to alterations of the skin microbiome and to a decrease in the epidermal barrier function.…”
Section: T Lymphocytessupporting
confidence: 89%
“…Combination of TLR ligand and allergic cytokine milieu further increased TSLP expression, indicating a potential mechanism for exacerbations in CH. 36 A recent study 17 comparing the transcriptome of lesion CH skin to skin from healthy controls has demonstrated important changes in the barrier epithelium: genes affecting processes of epithelial cell differentiation, desmosome organisation as well as regulation of epithelial morphogenesis were enriched, while, contrary to the situation in human AD, the expression of most of the genes involved in terminal differentiation of keratinocytes, such as filaggrin, involucrin and loricrin, was not changed in CH lesions compared to healthy skin. However, small prolinerich protein (SPRR), another component of the cornified layer, as well as other members of the SPRR family, were significantly upregulated in CH lesions.…”
Section: Epidermal Barriermentioning
confidence: 99%
See 1 more Smart Citation
“…One study in atopic horses showed ultrastructural abnormalities on electron microscopy when compared to normal horses [ 127 ] but it is unclear if this is the result of inflammation or may be suggestive of some primary impairment of the skin which could facilitate the epicutaneous absorption of the allergen and increased risk for allergic sensitization. A recently published study on horses with insect hypersensitivity compared the transcriptome in the epidermis of allergic horses with that of normal horses [ 128 ] and suggested skin impairment in insect allergic horses. It is possible that some of these allergic horses were also atopic.…”
Section: Horsesmentioning
confidence: 99%
“…For instance, a possible involvement of Dectin-1 in sterile inflammation and postpartum placenta retention was suggested in cows, since higher numbers of Dectin-1-expressing uterine macrophages were detected in retention-affected cows compared to cows with a regular afterbirth [ 85 ]. Allergic hypersensitivity and immunopathology can also be mediated by CTLs: in horses, Dectin-1, Dectin-2, and macrophage lectin 2 (MGL/Clec10a) may contribute to severe allergic dermatitis following insect bites [ 86 ]. Similar findings were also obtained for mice and men, as Dectin-1 −/− mice were largely protected against Aspergillus fumigatus -initiated corneal keratitis [ 87 ] and Dectin-1 blockade using the antagonist laminarin alleviated the severity of fungal keratitis in human patients [ 28 ].…”
Section: Detrimental Role Of Veterinary Relevant Ctlsmentioning
confidence: 99%